Reconciling Muslim Tradition and Modern Science: An Exploratory Study of Nidhal Guessoum’s Thought - Nur Rofiq; M. Zidny Nafi’ Hasbi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This paper aims to find out the results of Nidhal Guessoum's thoughts on his studies on Islam and contemporary science issues contained in his book entitled